Tephrostratigraphy and Magma Evolution Based on Combined Zircon Trace Element and U-Pb Age Data: Fingerprinting Miocene Silicic Pyroclastic Rocks in the Pannonian Basin - Lukács, Réka; Guillong, Marcel; Bachmann, Olivier; Fodor, László; Harangi, Szabolcs (Frontiers in Earth Science, 2021)
In this paper, we use LA-ICPMS analyses, a rapid and a cost-effective method, to obtain trace element contents and U-Pb ages of zircons for the main silicic ignimbrite units of the Bükkalja volcanic field, Pannonian basin, eastern-central Europe. This methodology of zircon fingerprinting offers a promising, previously-underestimated tephra correlation perspective, particularly in cases where the main minerals and glass are altered. In eastern-central Europe, more than 4000 km3 volcanic products were deposited in the Pannonian basin and its surroundings over 3 Myr during the early to mid-Miocene. We obtained distinct zircon trace element signatures for the main eruption units characterized by different magma (bulk rock) and melt (glass) compositions. Majority of zircon crystallized in evolved melts close to the solidus (680–750 oC). Multivariate discriminant analysis is proved to be useful to distinguish the main units and to correlate the unknown distal deposits based on selected trace elements and trace element ratios of zircon. This enabled to refine the formerly often ambiguous ages and stratigraphic relations of the scattered Miocene pyroclastic rocks in Northern Hungary. Using trace element content of zircons and glasses from the same samples of crystal-poor ignimbrites, we determined the zircon/melt partition coefficients. The obtained values of the distinct eruption units are very similar and comparable to published data for silicic volcanic systems. This suggests that zircon/melt partition coefficients in calc-alkaline dacitic to rhyolitic systems are not significantly influenced by the melt composition at >70 wt% SiO2. The partition coefficients and zircon trace element data can be used to calculate the equilibrium melt composition even where glass is thoroughly altered. and this data can be included in tephrostratigraphy. Furthermore, this technique is used to suggest that silicic magma reservoirs are often heterogeneous, not only thermally, but also compositionally. Melt lenses with distinct compositions develop in different parts of the magma reservoirs and could mix during eruption.